2005
DOI: 10.1007/s00535-005-1590-3
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated gastric carcinoma in the remnant stomach: de novo and metachronous gastric remnant carcinoma

Abstract: Epstein-Barr virus infection, together with long-standing inflammation, which causes GCP, may facilitate the development of de novo GRC. Close follow-up of patients treated with distal gastrectomy for EBV-associated GC is necessary to detect metachronous GRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…From the 5 studies 4043, 53 which also listed information on sex, the prevalence among stump/remnant cancers in males was estimated at 40% (± 7.44%). 3 studies included cases in females 40, 41, 43 where the EBV-positive cancer prevalence was 17% (± 9.6%).…”
Section: Resultsmentioning
confidence: 99%
“…From the 5 studies 4043, 53 which also listed information on sex, the prevalence among stump/remnant cancers in males was estimated at 40% (± 7.44%). 3 studies included cases in females 40, 41, 43 where the EBV-positive cancer prevalence was 17% (± 9.6%).…”
Section: Resultsmentioning
confidence: 99%
“…51 Besides, gastritis cystica polyposa, which is frequently observed in the remnant stomach, especially with Billroth II anastomosis, might be a prerequisite for the development of EBVaGC. 52 …”
Section: Epidemiological Features Of Ebvagc In Grcmentioning
confidence: 97%
“…Kaizaki et al found that the Epstein-Barr virus (EBV) was also associated with de novo and metachronous RGC [45]. EBV infection, along with longstanding inflammation, which causes primary gastric cancer, may facilitate the development of de novo RGC.…”
Section: Molecular Carcinogenesis Of Rgcmentioning
confidence: 99%